Experimental study on the effect of sugarcane bagasse ash (SBA) as partial cement substitute on concrete strength - Bernardez, Krizel Anne C.; Mendoza, Jacquelin A.; Candelaria, Ma. Doreen E. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Concrete is the most widely utilized construction material because of its durability and versatility. The dependence of the construction industry on concrete affects the demand for cement as its major component. However, cement production is hardly a sustainable process as it exploits naturally-occurring minerals. The process also emits immense carbon dioxide that threatens the environment. A positive response to this dilemma is the partial replacement of cement with supplementary cementitious materials (SCM). Previous studies have considered sugarcane bagasse (SBA) ash as SCM due to its pozzolanic properties. This study determines the effect of using SBA as partial cement substitute on the compressive strength of concrete. The colelcted SBA was sieved and further ground to cement fineness. A chemical analysis was performed to determine conformity of the processed SBA to the standard specifications for pozzolanic materials for use in concrete as specified by ASTM C 618. The processed SBA was then used in concrete - replacing 10%, 20%, 30%, and 40% of the required weight of cement. The compressive strength of the concrete samples were determined after 7, 14, 28, and 56 days of curing. The results have shown that the high silica content found in the processed SBA have significantly contributed to the strength performance of concretes with partially replaced cement. It was found that concretes with 20% replacement of cement with SBA have significantly higher compressive strength than the control concrete after 56 days of curing. Furthermore, the study suggests that 30% of the required weight of cement may be partially replaced with SBA to produce concrete that is comparable to the ordinary Portland cement concrete (0% SBA) after 28 days of sufficient curing. The remarkable similarity in strength of the control and the concretes with up to 30% cement replacement confirms the pozzolanic reaction between SBA and cement. Furthermore, the filler effect of SBA due to its fineness has proved to produce a denser concrete. The study concludes that SBA is a suitable pozzolanic material and may be used as sustainable alternative material to cement without sacrificing the function and practicality of concrete. The partial replacement of cement may consequently reduce carbon emissions, conserve natural resources, and reduce the cost of construction materials for sustainable construction.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Bagasse; Concrete; Waste products as building materials